2021
DOI: 10.21203/rs.3.rs-680733/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomechanical Study of Cortical Bone Trajectory Screws in Intervertebral Fixation of Lumbar Tuberculosis

Abstract: BackgroundWe aimed to explore the biomechanical stability and advantages of cortical bone trajectory (CBT) screws in the treatment of lumbar spine tuberculosis and provide biomechanical basis for the choice of clinical fixation methods. Methods16 pig spine specimens (T12-L5) were selected to simulate the lumbar spine(L2-L3) tuberculosis bone destruction model in vitro. The 16 specimens were randomly divided into 4 groups, and short segments (pedicle screws of the diseased vertebrae) were assigned respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Berthoux et al reported that the elevated levels of glycan-speci c IgG antibody were found to be not only associated with urine protein excretion, but also with poor long-term renal outcomes [21]. Intertstingly, in this study, we observed that sIgG levels correlated negatively to proteinuria(r =-0.41, p < 0.001) ,which is in line with previous reports [8,9]. And further cox regression analysis demonstrated that, at the time of biopsy , high serum IgG was an independent protective factor for renal endpoint events.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Berthoux et al reported that the elevated levels of glycan-speci c IgG antibody were found to be not only associated with urine protein excretion, but also with poor long-term renal outcomes [21]. Intertstingly, in this study, we observed that sIgG levels correlated negatively to proteinuria(r =-0.41, p < 0.001) ,which is in line with previous reports [8,9]. And further cox regression analysis demonstrated that, at the time of biopsy , high serum IgG was an independent protective factor for renal endpoint events.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that Gd-IgA1 alone can not cause the onset and progression of IgA nephropathy [5], and the production of antiglycosylation speci c antibodies including IgG and the formation of circulating immune complexes are the critical steps [6,7]. Liu et al [8] observed that low serum level of IgG is independently associated with poor prognosis of IgAN, and similar results were found by our previous study based on data from one single center [9] . However, the sample sizes in former studies were relatively small and the relationship between sIgG concentration and patients' prognosis was still not fully investigated.…”
Section: Introductionsupporting
confidence: 76%